Perceived organizational support, employee work engagement and work life balance: Social exchange theory perspective - Endang Sulistiyani; Yusmar Ardhi Hidayat; Andi Setiawan; Suwardi Suwardi (Universitas Semarang, 2022)
This study aimed to determine the effect of the Employee Work Engagement variable as a mediating variable between Perceived Organizational Support and Work-Life Balance. This type of quantitative descriptive research with Structural Equation Modeling as a data processing approach. The sampling technique is purposive sampling. They collected data by distributing questionnaires to 200 security unit employees working at State and Private Universities in Semarang City. The results showed a significant positive effect between the variables perceived organisational support, employee work engagement and work-life balance. The significant positive effect of the relationship between the three variables indicates that the employee work engagement variable can mediate the relationship between Perceived Organizational Support and Work-Life Balance. The triadic process between organisational support, work involvement and work-life balance is an implementation of social exchange theory. Employees give their time, energy, thoughts and enthusiasm for the organisation's benefit. Organisations provide remuneration in the form of compensation and welfare for the persistence of employee work for the advancement of the organisation. It gives a sense of satisfaction and happiness and can be used for yourself and your family. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh variabel Employee Work Engagement sebagai variabel mediasi antara Perceived Organizational Support dan Work-life Balance. Jenis penelitian deskriptif kuantitatif dengan Structural Equation Modeling sebagai pendekatan pengolahan data. Teknik pengambilan sampel adalah purposive sampling. Metode pengumpulan data dengan menyebarkan kuesioner kepada 200 pegawai satpam yang bekerja di Perguruan Tinggi Negeri dan Swasta di Kota Semarang. Hasil menunjukkan ada pengaruh positif signifikan antara variabel persepsi dukungan organisasi, employee work engagement dan work-life balance. Pengaruh positif signifikan pada hubungan ketiga variabel tersebut menunjukkan bahwa variabel employee work engagement mampu memediasi hubungan Perceived Organizational Support dan Work-life Balance. Proses triadik antara dukungan organisasi, keterlibatan kerja dan keseimbangan kehidupan kerja merupakan implementasi dari teori pertukaran sosial. Karyawan memberikan waktu, tenaga, pikiran dan semangat untuk kepentingan organisasi. Organisasi memberikan remunerasi berupa kompensasi dan kesejahteraan pada karyawan serta memberikan rasa kepuasan dan kebahagiaan yang dapat digunakan untuk diri sendiri dan keluarga.